Teaching thermal physics to Year 9 students: the thinking frames approach - McLure, Felicity; Won, Mihye; Treagust, David (Institute of Physics Publishing, 2020)
Students hold many alternative conceptions of thermal physics which are very resistant to change. A conceptual change strategy, the thinking frames approach, based on evidence from educational research was used to address commonly held naïve conceptions about heat in a series of thermal physics lessons. Students' gains in conceptual understanding were measured in two Year 9 classes using pre/post-tests. These results were compared to conceptual gains of a class learning the same topics by more traditional means. Results showed that learning thermal physics with the thinking frames approach led to a much greater increase in understanding (Effect size  =  2.04) compared to learning with traditional methods (Effect size  =  0.20).